Max Weber and the Idea of Economic Sociology - Swedberg, Richard (Book collections on Project MUSE., 2000)
While most people are familiar with The Protestant Ethic and the Spirit of Capitalism, few know that during the last decade of his life Max Weber (1864-1920) also tried to develop a new way of analyzing economic phenomena, which he termed "economic sociology." Indeed, this effort occupies the central place in Weber's thought during the years just before his death. Richard Swedberg here offers a critical presentation and the first major study of this fascinating part of Weber's work. Swedberg furthermore discusses similarities and differences between Weber's economic sociology and present-day thinking on the same topic. In addition, the author shows how economic sociology has recently gained greater credibility as economists and sociologists have begun to collaborate in studying problems of organizations, political structures, social problems, and economic culture more generally. Swedberg's book will be sure to further this new cooperation